MULTI-FRONTAL SOLVER FOR SIMULATIONS OF LINEAR ELASTICITY COUPLED WITH ACOUSTICS - Paszyński, Maciej; Jurczyk, Tomasz; Pardo, David (Computer Science, 2013)
This paper describes the concurrent multi-frontal direct solver algorithm for a multi-physicsFinite Element Method (FEM). The multi-physics FEM utilizes different element sizes aswell as polynomial orders of approximation over element edges, faces, and interiors (elementnodes). The solver is based on the concept of a node, and management of unknowns isrealized at the level of nodes. The solver is tested on a challenging multi-physis problem:acoustics coupled with linear elasticity over a 3D ball shape domain.